Preeclampsia as a Manifestation of New-Onset Systemic Lupus Erythematosus during Pregnancy: A Case-Based Literature Review - Miyamoto, Taito; Hoshino, Tatsuji; Hayashi, Nobutaka; Oyama, Ruriko; Okunomiya, Asuka; Kitamura, Sachiko; Ohtake, Noriko; Suga, Mami; Miyamoto, Kazunao; Takaoka, Aki; Aoki, Takuya; Imamura, Yuko; et al. (American Journal of Perinatology Reports, 2015)
Abstract Introduction New-onset systemic lupus erythematosus (SLE) during pregnancy is rare and difficult to diagnose, especially in cases that manifest as preeclampsia. We report a patient with new-onset SLE that manifested as preeclampsia during pregnancy and provide a review of the literature to identify factors for a rapid diagnosis. Case A 32-year-old primigravid Japanese woman was diagnosed with severe preeclampsia and underwent emergent cesarean section at 29 weeks of gestation. Her hypertension and renal disorder gradually improved after the operation, but her thrombocytopenia and anemia worsened. SLE was diagnosed on postoperative day 5 by a comprehensive autoimmune workup. She was discharged on postoperative day 34 with remission. Conclusion Our case and previous reports suggest that distinguishing underlying SLE from preeclampsia in the third trimester is particularly difficult. Helpful factors for diagnosis of suspected SLE in these cases were persistence of symptoms and new atypical symptoms for preeclampsia revealed after delivery (e.g., fever, renal disorder, and thrombocytopenia).